2020
DOI: 10.1101/2020.05.16.099788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nrf2 Activator PB125®as a Potential Therapeutic Agent Against COVID-19

Abstract: Nrf2 is a transcription factor that regulates cellular redox balance and the expression of a wide array of genes involved in immunity and inflammation, including antiviral actions. Nrf2 activity declines with age, making the elderly more susceptible to oxidative stress-mediated diseases, which include type 2 diabetes, chronic inflammation, and viral infections. Published evidence suggests that Nrf2 activity may regulate important mechanisms affecting viral susceptibility and replication. We examined gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 66 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…This leads to the activation of host antioxidant pathways including nuclear factor erythroid 2p45-related factor 2 (Nrf2) (Lee 2018). Nrf2 transcription factor is known to control the expression of various genes involved in antiviral actions (McCord et al 2020). A study conducted by McCord and colleagues showed that potent Nrf2 activation by PB125 ® compound downregulated ACE2 and TMPRSS2 mRNA expression in human liver-derived HepG2 cells.…”
Section: Garlic Oilmentioning
confidence: 99%
“…This leads to the activation of host antioxidant pathways including nuclear factor erythroid 2p45-related factor 2 (Nrf2) (Lee 2018). Nrf2 transcription factor is known to control the expression of various genes involved in antiviral actions (McCord et al 2020). A study conducted by McCord and colleagues showed that potent Nrf2 activation by PB125 ® compound downregulated ACE2 and TMPRSS2 mRNA expression in human liver-derived HepG2 cells.…”
Section: Garlic Oilmentioning
confidence: 99%
“…In this context, a vicious cycle of demethylation and augmented oxidative stress could increase susceptibility to SARS-CoV-2 infection [129]. Moreover, the antioxidant capacity is usually lost with age, and this pro-oxidative state associated with aging could be one of the reasons for which elderly people are more susceptible to being affected by SARS-CoV-2 infection [130][131][132].…”
Section: Interrelation Among Oxidative Stress Raas and Sars-cov-2 Imentioning
confidence: 99%
“…ARDS caused by SARS-Cov2 is followed by alveolar cells damage and lung fibrosis and the host immune response (with cytokine storm) and inflammation is a crucial determinant of disease outcome. Cytokine [26]. Nrf2 activation reduce lung cells damage in COVID-19 patients and Inhibits virus penetration.…”
Section: Discussionmentioning
confidence: 99%